Sastra Sebagai Jembatan Lintas Generasi: Strategi Pengajaran untuk Menghubungkan Siswa dengan Warisan Budaya - Lailiyah, Nur; Sasongko, Sempu Dwi; Pradana, Dimas Sandi (Universitas Nusantara PGRI Kediri, 2024)
In the fast-paced era of globalization, there is a concern that the younger generation is increasingly being uprooted from their cultural roots and ancestral heritage. This study aims to explore the potential of literary works as a bridge between generations, as well as propose effective teaching strategies to connect students with cultural heritage through literary works. The study involved 5 literature teachers and 50 students of SMK Negeri 1 Kediri. The study used a qualitative approach by analyzing data from classroom observations, interviews with teachers and students, and content analysis of literary works used in learning. Data collection was conducted for 3 months, from March to May 2024. The data analysis technique used was thematic analysis to identify patterns and themes in the data, which was then combined with content analysis of the literary works studied. The results showed that the use of classic and contemporary literary works rich in local cultural content can help increase students' appreciation of their cultural heritage. Effective teaching strategies include guided discussions, culture-based projects and collaboration with cultural resource persons. This research contributes to the understanding of the role of literature in bridging the intergenerational gap and promoting the preservation of cultural heritage through education.